2015
DOI: 10.3233/bme-151354
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of stress distribution in four different endodontic post systems in a model canine

Abstract: Abstract.To investigate the stress distribution in a maxillary canine restored with each of four different post systems at different levels of alveolar bone loss. Two-dimensional finite element analysis (FEA) was performed by modeling a severely damaged canine with four different post systems: CAD/CAM zirconia, CAD/CAM glass fiber, cast titanium, and cast gold. A force of 100 N was applied to the crown, and the von Mises stresses were obtained. FEA revealed that the CAD/CAM zirconia post system produced the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…To our knowledge, no previous study has investigated direct scanning of the post space. Several studies used different indirect techniques for digital data acquisition of the post space (23)(24)(25)(26)(27)(28)34). Lee et al scanned stone models of the post space to custom-fabricate the fiber post and core restoration (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, no previous study has investigated direct scanning of the post space. Several studies used different indirect techniques for digital data acquisition of the post space (23)(24)(25)(26)(27)(28)34). Lee et al scanned stone models of the post space to custom-fabricate the fiber post and core restoration (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Bittner et al (34), acrylic resin patterns were scanned to CAD/ CAM-fabricate a zirconia post and core. The scanning methods used were not specified in recent studies of CAD/CAM glass fiber posts by Chen et al (27,28). In addition, no studies have examined the usefulness of procedures for digital acquisition of the post space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 However, Chen et al reported that CAD/CAM glass fiber post is produce to stress in dentin, and is least recommended because of stress level. 34 As a result of this study, glass and carbon fiber post were showed homogeneous stress distribution. However, the values of the Von Mises stresses of glass fiber post were found higher than carbon fiber post.…”
Section: Discussionmentioning
confidence: 60%